Web-Based Expert System Application for Early Diagnosis of HIV/AIDS Using the Naive Bayes Method - Aisah, Sri Purwani; Adek, Rizal Tjut; Yunizar, Zara (Journal of Advanced Computer Knowledge and Algorithms, 2024)
AIDS is a progressive decrease in the immune system so that opportunistic infections can appear and end in death, therefore the author created an early diagnosis system for HIV/AIDS using the website-based Naïve Bayes algorithm. Naïve Bayes is a simple probability classification that can calculate all possibilities by combining a number of combinations and frequencies of a value from the database obtained.the results of the research obtainedThe naïve Bayes algorithm can be implemented for early diagnosis of HIV/AIDS by means that the existing HIV/AIDS symptom data is adjusted to the patient's symptom data processed using the naïve Bayes algorithm and then it is concluded what the symptoms are and What is the solution.